161 Single-Cell RNA-seq Highlights Immune-Driven Gender Differences in Glioblastoma. (April 2023) - Wang, Elaina; Young, Jacob; Chen, Jia-Shu; Aghi, Manish Kumar
Abstract : INTRODUCTION: Glioblastoma (GBM) is the most common primary malignant brain tumor and has a 1.6-fold higher incidence and shorter survival in men versus women. Gene expression differences may contribute to gender-specific differences. METHODS: Single cell RNA-sequencing (scRNA-seq) was conducted on 19, 642 cells from primary IDH-wild type GBM patients of both sexes (n = 11 total, 5 men and 6 women). A two-sample t-test was conducted on average age between sexes. Kaplan-Meier curves were used to evaluate survival between sexes. Bulk RNA-sequencing data was accessed via The Cancer Genome Atlas GBM dataset. Functional enrichment analyses were conducted on both scRNA and bulk RNA-seq data to determine relevant pathways from upregulated genes and visualized as gene concept networks via R. RESULTS: There was no difference in age (63.8 versus 53.8 years in men and women respectively) and survival (24 versus 26 months in men and women respectively). scRNA-seq functional enrichment analysis revealed myeloid cell upregulation in men and increased expression of angiogenesis genes such as ADM in women. There was no difference in T cell gene expression between sexes. Bulk RNA-seq analysis of 90 men and 50 women revealed marked elevation of immunoglobulin genes in men and innate genes such as M1 marker NOS2 in women. CONCLUSIONS: Innate myeloid and adaptive humoral components are highly upregulated in men with GBM compared to women, with no differences seen in T cell expression between sexes. This may contribute to higher incidences and shorter survival in men versus women, which should be accounted for in clinical trial evaluation.